STEM PROFESSIONAL DEVELOPMENT FOR K-12 TEACHERS: An Online Flipped Learning Model - Yıldırım, Bekir (Taylor and Francis, 2026)
This chapter presents the online flipped science, technology, engineering, and mathematics (STEM) Teacher Training Institute model designed to support professional development in STEM education. In developing this model, the flipped learning model and the eight stages of the STEM Teacher Training Institute model were integrated holistically. In the asynchronous part of the model, videos related to conceptual knowledge were included, whereas activities and practices were incorporated in the synchronous part to ensure high-quality professional development. An example of the instructional process for STEM teacher education is provided, along with recommendations based on the process. © 2026 selection and editorial matter, Heejung An and Woonhe Sung; individual chapters, the contributors.
Keywords: E-Learning; Engineering Education; Learning Systems; Professional Aspects; Stem (Science, Technology, Engineering And Mathematics); Teaching; Engineering And Mathematics; Engineering Teachers; K-12 Teachers; Learning Models; Mathematics Teacher; Professional Development; Science Education; Science Teachers; Science Technologies; Teacher Training; Personnel Training